Students’ Pronunciation Variations of Fricative Labiodental and Fricative Palato-Alveolar Sounds - Maryanti Mokoagouw; Jane Elisya Evaay; Sukristiningsih (Universitas Tidar, 2022)
This study aims at finding out the pronunciation variations on labiodental and palato-alveolar sounds produced by Year 2020 students of English Education Department University of Papua (UNIPA). The data were collected through the recording of students pronouncing lists of provided vocabulary of intended sounds. Ten students participated in the research. The research results show that students produced some pronunciation variations of both fricative labiodental and fricative palato-alveolar sounds. The most pronunciation variation occurs in the sound of fricative palato-alveolar voiced [ʒ]. Keywords: pronunciation variations,fricative, labiodental, palato-alveolar